Complementary configuration and performance comparison of CCHP-ORC system with a ground source heat pump under three energy management modes. (1st March 2017) - Kang, Ligai; Yang, Junhong; An, Qingsong; Deng, Shuai; Zhao, Jun; Li, Zelin; Wang, Yongzhen
Highlights: We presented a complementary CCHP-ORC system. The CCHP-ORC system is modeled using a comprehensive matrix approach. The improved mode performs better than thermal and electric energy management. Sensitivity analysis of operational cost is studied with electric and gas price. Abstract: The variation of the end-user load and the constant output of power generation units (PGUs) results in a mismatch between energy supply and demand. To reduce the difference and to avoid an excess output of electricity or heat, a complementary combined cooling, heating and power- organic Rankine cycle system (CCHP-ORC) system with a ground source heat pump is configured. In this study, the CCHP-ORC system, which is operated in thermal demand management (TDM) or electricity demand management mode, is employed to analyze the operational cost (OC), annual total cost (ATC), carbon dioxide emission (CDE), primary energy consumption (PEC) and system efficiency based on a case study of a regional energy system in Sino-Singapore eco-city. Meanwhile, the performance analysis of an improved operational mode is also conducted in this study. Following this mode, the waste heat and electricity imported from grid can be minimized by controlling the operation condition of PGU and ORC with a thermal management controller (TMC-ORC mode). Monthly and annual results in the case study show that the proposed system performed well on OC, CDE and PEC reductions and the ATC are both increased except for the ATC of TMC-ORC mode. However, the total efficiency of TDM is the highest among the three operational modes. Finally, for TMC-ORC mode, sensitivity analysis is performed and results are presented with varying electricity and gas price.